Students as partners of research projects in Russian universities: opportunities and barriers - Polina A. Ambarova; Nina V. Shabrova (Социологическая наука и социальная практика)
The article shows the potential and barriers to the realization of the conception, treating students as partners in research projects of universities. The foreign experience of implementing this conception in various spheres of academic life is presented. The positive effects and limitations of the conception of students as partners in research are summarized. Based on the results of the empirical study «Scientific mentoring in Russian universities: institutional models, professional roles, everyday practices», the prerequisites and barriers to the implementation of this concept in Russian universities are identified. The administrative, economic and social barriers caused by both the institutional and organizational conditions for the implementation of university science and the peculiarities of the established model of relationships in the academic environment between different generations of researchers are revealed. The positive impact of student involvement in grant projects is shown. It is proved that this form of interaction between “adults” and young researchers creates prerequisites for the implementation of the principles of the concept of students as university partners.